In-syringe-stirring: a novel approach for magnetic stirring-assisted dispersive liquid-liquid microextraction - Horstkotte, Burkhard; Suárez, Ruth; Solich, Petr; Cerdà, Víctor (Analytica chimica acta, 2013)
For the first time, the use of a magnetic stirrer within the syringe of an automated syringe pump and the resulting possible analytical applications are described. A simple instrumentation following roughly the one from sequential injection analyzer systems is used in combination with an adaptor, which is placed onto the barrel of a glass syringe. Swirling around the longitudinal axis of the syringe and holding two strong neodymium magnets, it causes a rotating magnetic field and serves as driver for a magnetic stirring bar placed inside of the syringe. In a first study it was shown that this approach leads to a sealed but also automatically adaptable reaction vessel, the syringe, in which rapid and homogeneous mixing of sample with the required reagents within short time can be carried out. In a second study in-a-syringe magnetic stirring-assisted dispersive liquid-liquid microextraction (MSA-DLLME) was demonstrated by the application of the analyzer system to fluorimetric determination of aluminum in seawater samples using lumogallion. A linear working range up to 1.1 μmol L(-1) and a limit of detection of 6.1 nmol L(-1) were found. An average recovery of 106.0% was achieved for coastal seawaters with a reproducibility of 4.4%. The procedure lasted 210 s including syringe cleaning and only 150 μL of hexanol and 4.1 mL of sample were required.
Keywords: Equipment Design; Seawater; hliník; Aluminum; Reproducibility of Results; Time Factors; časové faktory; Buffers; mikroextrakce kapalné fáze; Lumogallion; Liquid Phase Microextraction; reprodukovatelnost výsledků; limita detekce; Magnetics; Single-drop extraction; magnetismus; Limit of Detection; mořská voda; pufry; design vybavení; injekční stříkačky; In-syringe magnetic stirring-assisted liquid–liquid microextraction; Syringes